TOURIST PERCEPTIONS ON SEAGRASS ECOSYSTEMS IN THE BEACH TOURISM AREA, BINTAN REGENCY, RIAU ISLANDS - Khairunnisa, Khairunnisa; Yuda, Ardi Oksa; Haidawati, Haidawati; Arkham, Muhammad Nur (Politeknik Kelautan dan Perikanan Dumai, 2024)
Bintan Regency is one of the regencies in the Riau Islands Province which has a diversity of aquatic ecosystems, one of them is the seagrass ecosystem. The existence of seagrass beds is vulnerable to human activities, especially if tourists around the seagrass ecosystem are less aware of the importance of the existence of seagrass ecosystems. The research aim to determine tourists' perceptions of seagrass ecosystems in the coastal tourism area of Bintan Regency, Riau Islands Province. This research was carried out in December 2021-January 2022 along Trikora Beach. Data analysis used is descriptive quantitative analysis using a Likert scale. Based on the results of the study it can be concluded that tourists' perceptions of seagrass ecosystems in the coastal tourism area of Bintan Regency, namely knowledge 42.29% are in the sufficient category, cleanliness is 67.14% in the good category, beauty is 64.43% in the good category, environmental conditions are 71, 05% in the good category, and 61.72% benefits are in the good category.